A case of overlapping adult‐onset linear scleroderma and Parry‐Romberg syndrome presenting with widespread ipsilateral neurogenic involvement. Issue 1 (27th November 2019) - Yamasaki, Ryo; Yonekawa, Tomomi; Inamizu, Saeko; Shinoda, Koji; Ochi, Hirofumi; Matsushita, Takuya; Isobe, Noriko; Tsuji, Gaku; Sadashima, Shoko; Kuma, Yuki; Oda, Yoshinao; Iwaki, Toru; et al.
Abstract : Linear scleroderma is a variant of localized scleroderma. We report a 43‐year‐old woman who had developed left arm weakness and linear scleroderma on her back during pregnancy at 25 years of age, followed by left hemifacial atrophy and left leg weakness. She had multiple linear scleroderma lesions on her trunk and left limbs, left eyelid ptosis, impairment of vertical movement and abduction of the left eye, left hemifacial atrophy, and weakness and atrophy of the sternocleidomastoid, trapezius, and proximal limb muscles on the left side. On serology, antibodies to U1‐ribonucleoprotein and Jo‐1 were positive; anti‐scleroderma‐70 antibody was negative. Skin biopsy demonstrated increased hypertrophic collagen fibers without inflammatory infiltrates. Needle electromyography of left limb muscles revealed mild neurogenic patterns; left quadriceps muscle biopsy showed chronic neurogenic changes. Brain magnetic resonance imaging revealed mild left hemispheric atrophy. This is a rare case of linear scleroderma and Parry–Romberg syndrome presenting with widespread ipsilateral neurogenic manifestations.